On Compatibility Between University and Sustainability: Contentions, Opportunities, and Directions - Jung Hsiao (National Taipei University of Education, 2017)
The advocates of sustainability have started to regard universities as an important means to realize sustainable development since the Tbilisi Declaration in 1977, making universities a target of many initiatives to this day. However, as this study argues in accordance with the result of literature review, this phenomenon is politically correct as much as controversial. The reason lies in the fundamental question about the nature of university. In other words, the talk about how to realize the ideal of sustainable development through universities has to involve first the question of "what is the paradigm for universities?" As this study argues in light of rudimentary inquiries of the three paradigms and the reflection on educational philosophy, the university is better when it is based on the paradigm of "liberal education" rather than that of "knowledge factory" or "pragmatism." The study suggests that universities should adhere to the paradigm of liberation education as the most appropriate response to the ideal of sustainable development. Not only so, this study further points out what universities can do on the basis of their roles in the society: a member in the society, a vocational education institution, a training center for future leaders, and an organization for humanity and knowledge. It is especially worth noting that universities have potentials and advantages for the development of humanities and environmental ethics that are yet to be discovered and expanded.